Dynamics and coexistence in a system with intraguild mutualism - Assaneo, Florencia; Coutinho, Renato Mendes [UNESP]; Lin, Yangchen; Mantilla, Carlos; Lutscher, Frithjof (Elsevier, 2013)
It is a tenet of ecological theory that two competing consumers cannot stably coexist on a single limiting resource in a homogeneous environment. Many mechanisms and processes have since been evoked and studied, empirically and theoretically, to explain species coexistence and the observed biological diversity. Facilitative interactions clearly have the potential to enhance coexistence. Yet, even though mutual facilitation between species of the same guild is widely documented empirically, the subject has received very little theoretical attention. Here, we study one form of intraguild mutualism in the simplest possibly community module of one resource and two consumers. We incorporate mutualism as enhanced consumption in the presence of the other consumers. We find that intraguild mutualism can (a) significantly enhance coexistence of consumers, (b) induce cyclic dynamics, and (c) give rise to a bi-stability (a 'joint' Allee effect) and potentially catastrophic collapse of both consumer species. © 2012 Elsevier B.V.
Keywords: Allee effect; Complex dynamics; Facilitation; Intraguild mutualism; Species coexistence